2020
DOI: 10.1186/s12957-020-01893-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of distant metastasis after surgery among different breast cancer subtypes: a hospital-based study in Indonesia

Abstract: Background: More than one third of breast cancer patients including those that are diagnosed in early stages will develop distant metastasis. Patterns of distant metastasis and the associated risks according to the molecular subtypes are not completely revealed particularly in populations of patients with delayed diagnosis and advanced stages. Methods: Breast cancer patients (n = 1304) admitted to our institute (2014-2017) were evaluated to identify the metastatic patterns and the associated risks. Metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 59 publications
2
26
2
4
Order By: Relevance
“…According to the clinical characteristics of primary cancer, patients with bilateral breast cancer were more frequently diagnosed in more advanced diseases, although the significant association was found only in the tumor size (T status, Table 3 ). Our last results might indicate the involvement of metastatic process of cancer cells in the development of contralateral cancer because the risk factors are overlapping with risks of distant spread as shown in our previous report [ 8 , 15 ]. However, some studies reported a lack of association between advanced tumor and risk of bilateral cancer [ 5 , 12 , 16 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…According to the clinical characteristics of primary cancer, patients with bilateral breast cancer were more frequently diagnosed in more advanced diseases, although the significant association was found only in the tumor size (T status, Table 3 ). Our last results might indicate the involvement of metastatic process of cancer cells in the development of contralateral cancer because the risk factors are overlapping with risks of distant spread as shown in our previous report [ 8 , 15 ]. However, some studies reported a lack of association between advanced tumor and risk of bilateral cancer [ 5 , 12 , 16 ].…”
Section: Discussionsupporting
confidence: 74%
“…Demographic and clinicopathologic data including the patient's age, tumor size, stage, histological type, axillary lymph node involvement, and presence or absence of distant metastasis at the initial primary breast cancer (first tumor) and the contralateral cancer (second cancer) as well as administered treatment were collected from the medical records. Grouping of stages, histological type, tumor grade, immunohistochemistry of hormonal receptors, breast cancer subtypes as well as demographic variables was performed as previously reported [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our country (Indonesia), almost 350,000 new cases and 208,000 deaths were reported due to cancer [ 2 ]. Triple-negative breast cancer has especially attracted more attention due to the high mortality in females [ 3 ]. The high expression of the matrix metalloproteinase9 (MMP9) protein is one of the indicators during diagnosis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of patients with breast cancer will eventually develop distant metastasis including those who are diagnosed in early stages [ 1 ]. Patterns of locoregional recurrence and distant metastasis in patients with breast cancer vary depending on the tumor size, lymph node infiltration, histological subtype, differentiation grades, status of resection margin, immune response, lymphovascular invasion, and intrinsic molecular subtypes [ 2 ]. Also, social determinants causing non-adherence in breast cancer treatment have been associated with a higher risk of distant spread and poor functional well-being [ 3 ].…”
Section: Introductionmentioning
confidence: 99%